1983
DOI: 10.1080/00207598308247481
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of ‘Exchange‐orientation’ and ‘Commitment’ Scales to Marriage Adjustment*

Abstract: Believing that “exchange” and “commitment” are basic dimensions associated with marriage adjustment (MA), scales measuring these three dimensions were administered to 40 married couples. Exchange was predicted to be negatively correlated with MA, commitment positively associated with it, and an individual's exchange and commitment qualities were predicted to affect his partner's MA. The hypotheses were all supported. Further analyses, however, revealed that husbands' MA was more strongly associated with their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…In marriage, however, E was found to be negatively related to marriage adjustment. Subsequent research supported the negative association between E and marriage adjustment (Murstein and MacDonald, 1983) and between E and pair commitment among unmarried cohabitors (Milardo and Murstein, 1979).…”
mentioning
confidence: 81%
“…In marriage, however, E was found to be negatively related to marriage adjustment. Subsequent research supported the negative association between E and marriage adjustment (Murstein and MacDonald, 1983) and between E and pair commitment among unmarried cohabitors (Milardo and Murstein, 1979).…”
mentioning
confidence: 81%
“…Moreover, partners' reported adherence to a communal norm—as well as their perceptions of their spouse's adherence to that norm—have been linked to greater relationship satisfaction (Clark et al, in press). Others' work has shown that high levels of the individual difference variable of exchange orientation are negatively related to satisfaction in close relationships (Buunk & Van Yperen, 1991; Murstein, Ceretto, & MacDonald, 1977; Murstein & MacDonald, 1984) and that insecure attachment interferes with the ability to follow communal norms comfortably, as well as to avoid exchange norms (Bartz & Lydon, 2006; Clark et al, in press).…”
Section: What Work On a Qualitative Distinction Between Communal And mentioning
confidence: 99%
“…Sensitivity to perceptions of imbalance in dyadic relationships has also been shown to differ with relationship orientation. Murstein and colleagues (Murstein, Cerreto, & MacDonald, 1977;Murstein & MacDonald, 1983;Murstein, Wadlin & Bond, 1987) have found that spouses who are high in "exchange orientation," which measures the preference for "tit for tat" exchanges, are more likely to report low satisfaction, poor adjustment, and less commitment to their marital relationships. Similar results were reported by Buunk and VanYperen (1991), who found that marital partners who were low in exchange orientation were, overall, more satisfied with their relationships and that perceptions of balance were related to marital satisfaction only for individuals who were high in exchange orientation.…”
Section: Balance Of Contributionsmentioning
confidence: 99%